Irreversible loss of hot ductility following simulated primary cooling of a C–Mn steel to temperatures above the ferrite transformation temperature - Lekganyane, K.M.; Mostert, R.J.; Siyasiya, C.W.; Banks, K.M. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2021)
A hot ductility study has been performed on a low carbon peritectic steel grade with the view to simulate the effect of a temperature drop in the region just below the mould on the reduction of area during simulated unbending of a continuous cast thick broad slab. A Gleeble 1500D thermomechanical simulator was used to subject cylindrical specimens to various thermal histories, which included a fast primary cooling cycle to various minimum temperatures, Tmin, followed by a temperature rebound cycle and a slow secondary cooling step up to the unbending temperature prior to straining at a constant strain rate. Poor ductility was found when primary cooling was terminated at 70 °C above the ferrite start transformation temperature for primary cooling. This loss of ductility was not recovered during the rebound heating or secondary cooling steps. Dilatometry was performed to investigate this observation and it was shown that a small amount of ferrite formed at low temperatures, during the rebound heating. The deterioration in ductility was determined to be due to the formation of these thin ferrite films on the prior austenite grain boundaries. Dilatometry was used to show that the ferrite films later transformed back to austenite and the irreversible loss of the hot ductility was attributed to finely dispersed second phase particles remaining in position where the ferrite films had initially formed on the austenite grain boundaries.